1984
DOI: 10.1038/hdy.1984.44
|View full text |Cite
|
Sign up to set email alerts
|

B chromosomes in Rattus fuscipes II. The transmission of B chromosomes to offspring and population studies: support for the “parasitic” model

Abstract: SUMMARYFemale R. fuscipes [in the laboratory] were observed to transmit B chromosomes to their offspring at a frequency greater than expected. In two natural populations described here, this accumulation of Bs appears to be countered by strong selection against B carrying rats which is apparent from the disproportionate loss of +B individuals from the population before the breeding season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Previous sudies revealed a non-random pattern of B-chromosome distribution (Nur 1969, Thomson 1984, and various biological reasons for this have been taken into account. Due to intraspecific variation in their presence and frequency among populations dwelling in different habitats, it has been frequently stated that B chromosomes have an adaptive significance (Darlington 1963, Gibson and Hewitt 1972, Miintzing 1974, Hutchinson 1975, Carter 1978.…”
Section: Discussionmentioning
confidence: 99%
“…Previous sudies revealed a non-random pattern of B-chromosome distribution (Nur 1969, Thomson 1984, and various biological reasons for this have been taken into account. Due to intraspecific variation in their presence and frequency among populations dwelling in different habitats, it has been frequently stated that B chromosomes have an adaptive significance (Darlington 1963, Gibson and Hewitt 1972, Miintzing 1974, Hutchinson 1975, Carter 1978.…”
Section: Discussionmentioning
confidence: 99%
“…However, reanalysis of these data, taking into account the inclusion of karyotypes of related eggs in an egg pod, suggested that there was only weak evidence of a rise in B-frequency between adults and autumn eggs and no change in frequency between autumn and spring eggs (see Shaw et a!., 1985). In Rattus fuscipes, individuals from natural populations were karyotyped before and after breeding (Thomson, 1984). Rats with B-chromosomes were found to be at least twice as likely to be lost from the population before breeding than rats without B-chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical manipulations become somewhat involved, and the role which B chromosomes may play is difficult to determine. This is particularly so because of the general deleterious effect that B chromosomes have on their hosts in many species, including Rattus fuscipes (Thomson, 1984).…”
Section: Methodsmentioning
confidence: 99%
“…It forms the background for a population study (Thomson, 1984) which gives an assessment of the fitness of B chromosome-bearing individuals in natural populations.…”
Section: Introductionmentioning
confidence: 99%